2015
DOI: 10.1007/s10072-015-2143-z
|View full text |Cite
|
Sign up to set email alerts
|

Triptan use among hospital workers affected by migraine

Abstract: Triptans represent the most specific and effective treatment for migraine attacks. Nevertheless, in clinical practice, they are often underused. Hospital workers, in particular physicians, are expected to be more aware of the correct use of specific drugs, especially for a very common disease such as migraine. Aim of this study was to evaluate whether different hospital workers affected by migraine are able to correctly manage the most suitable therapy for their migraine attacks. During a 1-year period, we sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Consequently, the use of specific molecules, such as triptans, presented a very low diffusion. These results reflect international literature, but on the other hand, underline a very unsatisfactory knowledge about migraine and its possible consequences[ 2 , 3 ]. Moreover, these data are especially worrisome because they are representative of a hospital population.…”
Section: Discussionsupporting
confidence: 83%
“…Consequently, the use of specific molecules, such as triptans, presented a very low diffusion. These results reflect international literature, but on the other hand, underline a very unsatisfactory knowledge about migraine and its possible consequences[ 2 , 3 ]. Moreover, these data are especially worrisome because they are representative of a hospital population.…”
Section: Discussionsupporting
confidence: 83%
“…Despite the impact of migraine on the different aspects of life, the self-consciousness of illness and the management turns out to be unsatisfactory: several studies report that only a negligible part of migraine patients refer to headache centres. 9 , 10 Moreover, studies regarding the pharmacologic treatment have shown that specific therapies for the acute attack of migraine, namely triptans, are underused. 11-13 Aim of this study was to investigate, in a population of hospital workers, the prevalence of headache and migraine, the management and the awareness of illness.…”
Section: Introductionmentioning
confidence: 99%